In silico investigation of wound healing potential of some compounds in tubers of Asphodelus species with GSK3-beta protein - AKSOY, HALİL; ŞEKERLER, TURGUT (MARMARA UNIV, 2021)
Wound healing is a process that involves biochemical processes such as inflammation and cell proliferation and is controlled by many proteins. It is known that one of the most effective factors in this process is the inhibition of GSK3-beta protein. In current study, in silico wound healing activity of the some compounds found in the tubers of Asphodelus species used as a wound healing in traditional medicine were investigated. For this purpose, the interactions between the compounds and GSK3-beta protein were studied in silico. As a result of the study, it has been determined that and stigmasterol, beta-sitosterol and emodin molecules are effective.
Keywords: Asphodelus species; beta-sitosterol; emodin; GSK3-beta protein; stigmasterol; wound healing activity; GLYCOGEN-SYNTHASE KINASE-3-BETA; DOCKING